Implementasi Fiqh Khiyâr dalam Praktik Jual Beli dengan Sistem Pesanan: Studi di Desa Gelangkulon Ponorogo - Andri Yurinta; Novi Fitia Maliha; Muhammad Aldo Arta Mardika (Fakultas Syariah Institut Agama Islam Negeri Ponorogo, 2022)
In the development of the era of buying and selling models have various kinds that apply in society. As is the case with the practice of buying and selling bricks in Gelangkulon Village, Sampung District, Ponorogo Regency, there are 2 types of contract models used in buying and selling bricks, namely: first, direct is a contract that is carried out directly between brick producers and brick buyers. indirectly between brick collectors and brick buyers. Brick collectors buy bricks from brick manufacturers who do not yet have customers. In indirect transactions, there is often a delay in the return of defective goods from the buyer and collectors also often provide compensation that is not in accordance with the amount of loss. Departing from this background, the authors are interested in conducting research with the title Application of Fiqh Khiyâr in the Practice of Buying and Selling Bricks with an Order System in Gelangkulon Village, Sampung District, Ponorogo Regency. The problems studied are the first, how is the khiyâr review of the delay in returning defective goods in the practice of buying and selling bricks with an order system in Gelangkulon Village, Sampung District, Ponorogo Regency?. Second, how is the khiyâr review of the provision of compensation for defective goods in the practice of buying and selling bricks with an order system?, This research is a field research, using a qualitative approach, namely collecting data through observation, interviews, and documentation. Data analysis using inductive method. The discussion of this research can be concluded that: First, the practice of khiyâr on delays in returning defective goods in buying and selling bricks in the village of Gelangkulon, Sampung, Ponorogo district, even though it has passed the time limit according to custom, is still enforced where collectors are still willing to provide compensation. Second, the practice of buying and selling bricks in Gelangkulon Village, Sampung District, Ponorogo Regency has implemented khiyâr. The khiyâr used is khiyâr 'aib, because the defective item is known after the delivery process. However, the application of khiyâr 'disgrace is not perfect, because the compensation is only half of the total amount of damage. Model praktik jual beli di masyarakat sangat beraneka macam. Seperti halnya pada praktik jual beli batu bata di Desa Gelangkulon, Ponorogo, ada 2 macam model akad yang digunakan dalam jual beli tersebut, yaitu: secara langsung (akad yang dilakukan secara langsung antara produsen batu bata dengan pembeli batu bata), dan secara tidak langsung (dilakukan antara pengepul batu bata dengan pembeli batu bata). Pengepul batu bata membeli batu bata dari produsen batu bata yang belum memiliki pelanggan. Dalam transaksi secara tidak langsung, sering dari terjadi keterlambatan pengembalian barang cacat dari pihak pembeli, serta pihak pengepul juga sering melakukan pemberian ganti rugi yang tidak sesuai dengan jumlah kerugian. Berdasarkan masalah tersebut, penulis tertarik melakukan penelitian dengan judul Implementasi Fiqh Khiyâr Dalam Praktik Jual Beli dengan Sistem Pesanan (Studi di Desa Gelangkulon, Ponorogo). Penelitian ini merupakan penelitian lapangan (field research), dengan menggunakan metode pendekatan kualitatif yaitu mengumpulkan data melalui observasi, wawancara, dan dokumentasi. Analisa data menggunakan metode induktif. Kesimpulan dari penelitian ini: Pertama, praktik khiyâr pada keterlambatan pengembalian barang cacat pada jual beli batu bata di Desa Gelangkulon, Ponorogo meskipun sudah melewati batas waktu menurut adat, tetap diberlakukan dimana pengepul tetap bersedia memberikan ganti rugi. Kedua, pada praktik jual beli batu bata di Desa Gelangkulon Kabupaten Ponorogo sudah menerapkan khiyâr. Khiyâr yang digunakan adalah khiyâr ‘aib, sebab barang cacat diketahui setelah proses pengiriman. Namun penerapan khiyâr ‘aib kurang sempurna, karena pemberian ganti rugi hanya setengah dari jumlah keseluruhan kerusakan.